German partner supports new ATIs for energy-efficient construction - Niediek, Silvia [Verfasser] (My University, 2016)
"The German organization BFW Bau Sachsen had been commissioned by the Indian Government to deliver a concept for an Advanced Training Institute (ATI) on Construction in India with special focus on energy-efficient construction technologies. The Indian Ministry of Skill Development and Entrepreneurship (MSDE) aimed at developing two ATIs in the states of West Bengal and Odisha with the German partner." (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 2.3.4 Asien; Berufsbildung; Internationale Zusammenarbeit; Indien; Bundesrepublik Deutschland